2021
DOI: 10.21833/ijaas.2021.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of risk of using computerized AIS on external auditor's work quality in Yemen

Abstract: This study aimed to identify the effect of the risks of using computerized AIS in facilities subject to auditing on external auditor's work quality. The study was applied to Yemeni external auditors, with a targeted sample size of 120 people who were randomly selected. Data were collected through questionnaires. The collected data were processed using SPSS version 23. The results of this study revealed a statistically significant effect of risk associated with the use of computerized AIS (human risks, environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Accounting information system (AIS) is a computerized IS concerned with the firm's financial and economic activities. According to Al-Hattami et al (2021b), AIS is a computer-based software application to input and process financial data to generate financial information. Grande et al (2011) identified AIS as a technological tool developed to manage and control issues related to the firm's financial and economic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Accounting information system (AIS) is a computerized IS concerned with the firm's financial and economic activities. According to Al-Hattami et al (2021b), AIS is a computer-based software application to input and process financial data to generate financial information. Grande et al (2011) identified AIS as a technological tool developed to manage and control issues related to the firm's financial and economic activities.…”
Section: Introductionmentioning
confidence: 99%
“…AIS is defined as a specific software application and management process which mainly aims to process data and provide the information required to make proper decisions, whether it is financial or administrative information from within the company (Belfo and Trigo, 2013; Trigo et al , 2014; Al-Hattami et al , 2021c). It is the lifeblood of an enterprise; without it, corporate activities could not be planned, coordinated or controlled (Al-Hattami et al , 2021c; Sarwar et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…AIS is defined as a specific software application and management process which mainly aims to process data and provide the information required to make proper decisions, whether it is financial or administrative information from within the company (Belfo and Trigo, 2013; Trigo et al , 2014; Al-Hattami et al , 2021c). It is the lifeblood of an enterprise; without it, corporate activities could not be planned, coordinated or controlled (Al-Hattami et al , 2021c; Sarwar et al , 2021). Indeed, the role of AIS is essential, not only for external investors or large companies but even for SMEs, as it provides crucial valuable information in the planning, control and decision-making stages (Almbaidin, 2014; Latifah et al , 2021; Monteiro and Cepêda, 2021; Thuan et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/2398-6247.htm provided (Feliciano and Quick, 2022;Al-Hattami et al, 2021). Information technology (IT) has received attention from firms, accountants, auditors, professional bodies, academics and regulators (Khan, 2018;Al-Hattami, 2022, 2023.…”
Section: Introductionmentioning
confidence: 99%